The Practicality of Popular Scientific Book of Fungi in Tabanio Beach Forest as Enrichment for Botani Tumbuhan Rendah Course - Putri Pratami Rahmiati; Yudi Firmanul Arifin; Atiek Winarti (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Learning resources can be developed by utilizing the surrounding environment or based on local potential. Individual intelligence will grow and develop through a process of interaction with their environment, so it is necessary to use the environment in contextual learning. One of the sources of learning based on local potential that can be developed is popular scientific books. The development of learning resources in the form of popular scientific books in this study aims to overcome the problem of limited learning resources in low plant botanical subjects, especially on the topic of fungi with macroscopic materials and examples of fungi from the environment. This development research aims to test the practicality of a popular scientific book entitled